Skin-to-blood pH shift triggers metabolome and proteome global remodelling in Staphylococcus epidermidis - Gonçalves, Luis Gafeira; Santos, Susana; Gomes, Laidson Paes; Armengaud, Jean; Miragaia, Maria; Coelho, Ana Varela (Frontiers in Microbiology, 2022)
Staphylococcus epidermidis (SE) is one of the most common bacteria of the human skin microbiota. Despite its role as a commensal, SE has emerged as an opportunistic pathogen, associated with 80% of medical devices related infections. Moreover, these bacteria are extremely difficult to treat due to their ability to form biofilms and accumulate resistance to almost all classes of antimicrobials. Thus new preventive and therapeutic strategies are urgently needed. However, the molecular mechanisms associated with SE colonisation and disease is still poorly understood. A deeper understanding of the metabolic and cellular processes associated with response to environmental factors characteristic of SE ecological niches in health and disease might provide new clues on colonisation and disease processes. Here we studied the impact of pH conditions, mimicking the skin pH (5.5) and blood pH (7.4), in a S. epidermidis commensal strain by means of next-generation proteomics and 1H NMR-based metabolomics. Moreover, we evaluated the metabolic changes occurring during a sudden pH change, simulating the skin barrier break produced by a catheter. We found that exposure of S. epidermidis to skin pH induced oxidative phosphorylation and biosynthesis of peptidoglycan, lipoteichoic acids and betaine. In contrast, at blood pH, the bacterial incorporation of monosaccharides and its oxidation by glycolysis and fermentation was promoted. Additionally, several proteins related to virulence and immune evasion, namely extracellular proteases and membrane iron transporters were more abundant at blood pH. In the situation of an abrupt skin-to-blood pH shift we observed the decrease in the osmolyte betaine and changes in the levels of several metabolites and proteins involved in redox cell homeostasis. Our results suggest that at the skin pH S. epidermidis cells are metabolically more active and adhesion is promoted, while at blood pH, metabolism is tuned down and cells have a more virulent profile. pH increase during commensal-to-pathogen conversion appears to be a critical environmental signal to the remodelling of the S. epidermidis metabolism towards a more pathogenic state. Targeting S. epidermidis proteins induced by a low alkaline pH and local acidification of medical devices microenvironment might be new strategies to treat and prevent S. epidermidis infections.